Model Komunikasi Dakwah Berbasis Desain Komunikasi Visual Pada Akun Instagram @Dailymuslimahindonesia - Annisa, Nurin (Jurnal Syntax Fusion, 2024)
Technological developments have brought new innovations in Islamic da'wah through Instagram social media. This research aims to analyze the elements and principles of visual communication design and da'wah communication models on the Instagram account @dailymuslimahindonesia. Da'wah that previously relied on conventional methods has now transformed by utilizing attractive visual design to convey Islamic messages to the younger generation. The research uses descriptive qualitative methods with content analysis techniques to examine visual content and communication models applied. Primary data was obtained through observation of Instagram posts and interviews with the account founder, while secondary data came from literature studies and documentation. Analysis was conducted based on visual communication design theory and Harold Lasswell's communication model. The results show that @dailymuslimahindonesia posts have fulfilled the elements of visual communication design including typography, lines, colors, textures, light-dark contrast, size, and form, as well as the principles of balance, emphasis, rhythm, and unity. This account has also implemented the five elements of Lasswell's communication model completely: who (Daily Muslimah Indonesia as communicator), says what (da'wah messages based on Quran, hadith, self-reminders, and sunnah fasting calendar), in which channel (Instagram platform), to whom (88 thousand followers from various backgrounds), and with what effect (positive feedback in the form of hijrah motivation and religious discussions). The research concludes that the combination of visual communication design with Islamic da'wah messages can be an effective medium for spreading religious values in the digital era, particularly in reaching the younger generation through attractive and easily understood visual content.